Optimal management of Barrett's esophagus: pharmacologic, endoscopic, and surgical interventions - Konda VJA; Dalal K (Dove Medical Press, 2011)
Vani JA Konda1, Kunal Dalal21Section of Gastroenterology, Department of Medicine, 2Department of Internal Medicine, University of Chicago Medical Center, Chicago, Illinois, USAAbstract: Esophageal adenocarcinoma and its precursor, Barrett's esophagus, are rapidly rising in incidence. This review serves to highlight the role of pharmacologic, endoscopic, and surgical intervention in the management of Barrett's esophagus, which requires acid suppression and endoscopic assessment. Treatment with a proton pump inhibitor may decrease acid exposure and delay the progression to dysplasia. Patients who require aspirin for cardioprotection or other indications may also benefit in terms of a protective effect against the development of esophageal cancer. However, without other indications, aspirin is not indicated solely to prevent cancer. A careful endoscopic examination should include assessment of any visible lesions in a Barrett's segment. An expert gastrointestinal pathologist should confirm neoplasia in the setting of Barrett's esophagus. For those patients with high-grade dysplasia or intramucosal carcinoma, careful consideration of endoscopic therapy or surgical therapy must be given. All visible lesions in the setting of dysplasia should be targeted with focal endoscopic mucosal resection for both accurate histopathologic diagnosis and treatment. The remainder of the Barrett's epithelium should be eradicated to address all synchronous and metachronous lesions. This may be done by tissue acquiring or nontissue acquiring means. Radiofrequency ablation has a positive benefit-risk profile for flat Barrett's esophagus. At this time, endoscopic therapy is not indicated for nondysplastic Barrett's esophagus. Esophagectomy is still reserved for selected cases with evidence of lymph node metastasis, unsuccessful endoscopic therapy, or with high-risk features of high-grade dysplasia or intramucosal carcinoma.Keywords: Barrett's esophagus, high-grade dysplasia, esophagectomy, ablation, endoscopic mucosal resection